2016
DOI: 10.1371/journal.pone.0166895
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Models for Tornado Climatology: Long and Short-Term Views

Abstract: This paper estimates regional tornado risk from records of past events using statistical models. First, a spatial model is fit to the tornado counts aggregated in counties with terms that control for changes in observational practices over time. Results provide a long-term view of risk that delineates the main tornado corridors in the United States where the expected annual rate exceeds two tornadoes per 10,000 square km. A few counties in the Texas Panhandle and central Kansas have annual rates that exceed fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
2
22
0
Order By: Relevance
“…Seasonal tornado counts were generated for winter (December of previous year, January, and February (DJF)) and spring (March, April, and May (MAM)). DJF and MAM are the focus of this study because previous studies illustrate that tornado counts and ENSO are related in these seasons [12][13][14][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Seasonal tornado counts were generated for winter (December of previous year, January, and February (DJF)) and spring (March, April, and May (MAM)). DJF and MAM are the focus of this study because previous studies illustrate that tornado counts and ENSO are related in these seasons [12][13][14][17][18][19].…”
Section: Methodsmentioning
confidence: 99%
“…Cook and Schaefer [16] later reported that winter tornado outbreaks were stronger and more frequent during the neutral phase (N) of ENSO, followed by the LN then EN phases. e most recent studies report that tornado activity is heightened during the LN phase [12][13][14][17][18][19]. Recent studies also illustrate that the seasons with the most tornadoes tend to be classified as LN.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations